Jejak Islamisasi Jawa Oleh KH Soleh Darat (Studi Kasus Naskah Kitab Syarah Al-Hikam) - Muhammad Abdullah (Program Studi Sastra Indonesia, Fakultas Ilmu Budaya, Universitas Diponegoro, 2018)
By translating many books of jurisprudence and Sufism in Javanese, KH Sholeh Darat delivered a message of da'wah at the house of the Regent of Demak which was the uncle of R.A. Kartini. KH Sholeh Darat translates the Quran in Javanese using Arabic Pegon. The book was recorded as the first translation book in the world in Javanese. The first book of interpretation in Arabic Javanese Pegon was given the name Faidhur Rohman. In his missionary ethos, KH Soleh Darat was very concerned about how Javanese culture and character education of Javanese people lack understanding in Arabic. Therefore, the effort to translate various books into banhasa Jawa is nothing more than the process of Javanese Islamization which is very accommodating to Javanese culture. One of the books that reveals the Javanese ethic of Sufism is the Syarah Al Hikam Book. This research is based on the consideration that the manuscript includes some of the cultural riches of the archipelago of the past century which until now can still be saved. Therefore, this manuscript needs to be studied philologically and thematically, especially the values of the propaganda of KH Sholeh Darat which provide a wind of harmony in religion. Through intertextual studies this study intends to find the character relationship of Syarah Al Hikam KH Soleh Darat. Through the learning of the Al Hikam book, traces of Islamic thought and the method of da'wah that combines Islamic culture and Javanese culture, accommodating, moderate, between the Shari'a and the tarekat is the harmonization of Islam can be accepted in the multicultural society in Semarang and Java in the 19th century.